The soluble CTLA-4 receptor and its role in autoimmune diseases: an update - Saverino, Daniele (Auto Immun Highlights, 2010)
CTLA-4, initially described as a membranebound molecule, is a costimulatory receptor transducing a potent inhibitory signal. Increasing evidence shows the CTLA-4 gene to be an important susceptibility locus for autoimmune endocrinopathies and other autoimmune disorders. A soluble form of cytotoxic T-lymphocyte-associated antigen-4 (sCTLA-4) has been established and shown to possess CD80/CD86 binding activity and in vitro immunoregulatory functions. sCTLA-4 is generated by alternatively spliced mRNA. Whereas low levels of sCTLA-4 are detected in normal human serum, increased serum levels are observed in several autoimmune diseases (e.g. Graves’ disease, myasthenia gravis, systemic lupus erythematosus, type 1 diabetes, systemic sclerosis, coeliac disease, autoimmune pancreatitis and primary biliary cirrhosis). The biological significance of increased sCTLA-4 serum levels is not fully clarified yet. On the one hand, it can be envisaged that sCTLA-4 specifically inhibits early T-cell activation by blocking the interaction of CD80/CD86 with the costimulatory receptor CD28. On the other hand, higher levels of sCTLA-4 could compete for the binding of the membrane form of CTLA-4 with CD80/CD86 in the later phases of T-lymphocyte activation, causing a reduction in inhibitory signalling. This double-edged nature of sCTLA-4 to block the binding of CD28 to CD80/CD86 may result in different outcomes during the clinical course of an autoimmune disease.